KAPITALISME RUNTUH EKONOMI SYARIAH BERKAH (Napaktilas Constitutum Menuju Constituendum) - Mashudi, Mashudi (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2013)
Constitutum means discuss, evaluate and assess the role of the law that had been in force in the community, whether in accordance with the needs of society or is precisely the opposite. While constituendum interpreted efforts to create a progressive law, the law is deemed effective welfare society. To develop and promote Islamic banks are at least teen pillars that must be considered, namely: improving service and professionalism, product innovation, human resources, expansion of branch network, which supports the legislation, Shariah compliance, continuous education, synergy, the results competitive, and reorientation to the real sector. If the government carry out its role effectively, it will be a positive contribution to the development of the community because of the need will be met, they will be motivated through the hard work of careful and efficient. However, if it is not done, then there is destruction. The resources needed for the countrys interests, acquired through the tax system fair and efficient. Similarly, if the world economy has been restless uneasy with capitalism and socialism, then ekomoni sharia in Indonesia should seriously empowered to oversee the welfare of the people.